The Relationship Of Knowledge And Behavior About Nutrition To The Event Of Anemia In Adolescent Women In The Environment V Bamboo Field New Neighborhood - Dwi Ris Hasanah S; Helena Fransysca (Institute of Computer Science (IOCS), 2020)
Nutrition or also called nutrition, is the study of food and its relationship to health. This study aims to determine the relationship of knowledge and behavior about nutrition to the incidence of anemia in adolescent girls. The research method used is pre-experimental with the design of